Comparison of Five Experimental Pain Tests to Measure Analgesic Effects of Alfentanil - Luginbühl, Martin; Schnider, Thomas W.; Petersen-Felix, Steen; Arendt-Nielsen, Lars; Zbinden, Alex M. (Anesthesiology (Philadelphia), 2001)
Several experimental pain models have been used to measure opioid effects in humans. The aim of the current study was to compare the qualities of five frequently used experimental pain tests to measure opioid effects. The increase of electrical, heat, and pressure pain tolerance and the decrease of ice-water and ischemic pain perception was determined at baseline and at four different plasma concentrations of alfentanil (n = 7) administered as target controlled infusion or placebo (n = 7). A linear mixed-effects modeling (NONMEM) was performed to detect drug, placebo, and time effect as well as interindividual and intraindividual variation of effect. Only the electrical, ice-water, and pressure pain tests are sensitive to assess a concentration-response curve of alfentanil. At a plasma alfentanil concentration of 100 ng/ml, the increase in pain tolerance compared with baseline was 42.0% for electrical pain, 22.2% for pressure pain, and 21.7% for ice-water pain. The slope of the linear concentration-response curve had an interindividual coefficient of variation of 58.3% in electrical pain, 35.6% in pressure pain, and 60.0% in ice-water pain. The residual error including intraindividual variation at an alfentanil concentration of 100 ng/ml was 19.4% for electrical pain, 6.1% for pressure pain, and 13.0% for ice-water pain. Electrical pain was affected by a significant placebo effect, and pressure pain was affected by a significant time effect. Electrical, pressure, and ice-water pain, but not ischemic and heat pain, provide significant concentration-response curves in the clinically relevant range of 200 ng/ml alfentanil or lower. The power to detect a clinically relevant shift of the curve is similar in the three tests. The appropriate test(s) for pharmacodynamic studies should be chosen according to the investigated drug(s) and the study design.